Physicochemical properties and antibiofilm activity of tricalcium silicate cement and its association with cetrimide = Propiedades físico-químicas y actividad antibiofilm del cemento de silicato tricálcico y su asociación con cetrimida - Bueno Rodrigues, Giulia; Tanomaru Filho, Mario; Chávez Andrade, Gisselle Moraima; Esteves Torres, Fernanda Ferrari; Guerreiro Tanomaru, Juliane Maria (2022)
Cetrimide (CTR) is a cationic surfactant detergent with antimicrobial and antibiofilm activity. The aim of this study was to evaluate setting time, pH, solubility and antibiofilm activity of tricalcium silicate cement (TSC) with zirconium oxide (ZrO2) and its association with 0.2 and 0.4% cetrimide. Initial and final setting times (IST and FST) were assessed based on ISO-6876. pH was evaluated at periods of 1,3,7,14 and 21 days. Solubility was analyzed by weight loss. A modified direct contact test (MDCT) on the biofilm of Enterococcus faecalis formed on bovine root dentin blocks was performed, after 6 hours of manipulation and 15 hours of contact time. The analysis was performed by UFC mL ̄¹ counting. The data were analyzed by ANOVA and Tukey's tests (α=0.05). Higher IST was observed for TSC/ZrO2+CTR in both concentrations than for TSC/ZrO2 and lower FST for TSC/ZrO2+0.4% CTR (p<0.05). On day 1, TSC/ZrO2 showed lower pH than the associations with CTR (p<0.05). During the other periods, TSC/ZrO2 and associations promoted similar alkalinization (p>0.05). All materials exhibited increased mass. TSC/ZrO2+CTR 0.4% had lower mass gain than the other materials (p<0.05). The highest antibiofilm activity was observed for TSC/ZrO2+CTR in both concentrations, when compared with the positive control (p<0.05). In conclusion, CTR exhibited potential to promote greater antibiofilm activity to tricalcium silicate cement, without harming its physicochemical properties of setting time, pH and solubility.
En revista Odóvtos, vol. 24, no.1 (enero-abril 2022)
Descripción basada en el contenido visto el 15 de noviembre, 2024
También disponible en formato HTML y EPUB